2019
DOI: 10.1108/bl-02-2019-0065
|View full text |Cite
|
Sign up to set email alerts
|

Schema

Abstract: This article reviews development of thinking about the information needed by companies to create an accurate picture of how well they manage their engagement with customers, taking into account the evolution of thinking and practice in this area over the last three decades towards the idea of data-driven customer engagement. It then describes the evolution and use of an assessment and benchmarking process and tool which provide the needed information. Design/methodology/approach: Literature review, conceptual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…Firms derive benefits from customers by launching ECMCs to engage and cooperate with them (Chenhall, 2005). Customer engagement gives brands value and competitive advantages by sharing information and involving their customers (Stone et al, 2019). The findings support the argument that customer engagement is a key factor in achieving strategic performance.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Firms derive benefits from customers by launching ECMCs to engage and cooperate with them (Chenhall, 2005). Customer engagement gives brands value and competitive advantages by sharing information and involving their customers (Stone et al, 2019). The findings support the argument that customer engagement is a key factor in achieving strategic performance.…”
Section: Discussionsupporting
confidence: 60%
“…Such customer engagement determines the level of strategic performance. Customer engagement is advantageous to brands by the information sharing and customer involvement it creates (Stone et al, 2019).…”
Section: Customer Engagement As a Mediator In The Relationship Betwee...mentioning
confidence: 99%
“…Patients with AML harboring internal tandem duplication (ITD) mutations of the FMS-related tyrosine kinase 3 gene ( FLT3 ) have short remission durations and poor OS. A recent phase 3 study showed that adding the multi-kinase inhibitor midostaurin to standard chemotherapy improved outcomes in patients with FLT3 -mutated AML, potentially leading to a new standard-of-care for this molecularly defined population. More selective FLT3 inhibitors such as quizartinib and gilteritinib have now entered late-stage development.…”
Section: New Targeted Therapiesmentioning
confidence: 99%